KONSEP BERPIKIR DALAM ALQURAN - Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
The term thinking as the root of the word think the meaningful intellect, memory, and then the word is laced with the prefix " ber " so be thinking the meaning of using reason to consider and decide something. The word matched by the term ratio, according to common sense reasoning, intellect, reason. Thinking is the essence of philosophy, while the purpose of philosophy is to find the absolute truth. Therefore the purpose of thinking is to seek the truth. Doing so with a view of the crisis on the universe and the phenomenon as well as the history of mankind, came to observe the inner side and outer side of human beings based on logical thinking, then obtained a science